Frontiers of violence conflict and identity in Ulster and Upper Silesia, 1918-1922 - Wilson, Tim, 1971- (Oxford historical monographs., 2010)
In the years after the First World War both Ulster & Upper Silesia saw violent conflicts over self-determination. Examining the nature of communal boundaries, such as religion & language Timothy Wilson explains the profound contrasts in these experiences of plebeian violence.